Bracia Mateccy - przedwojenni kupcy bydgoscy (Kronika Bydgoska, 2018)
The article is dedicated to the Matecki family, still remembered by the residents of Bydgoszcz, which before World War II was involved in commercial activities. They made history as the owners of the Bydgoszcz Department Store. The history of the Matecki family is an example of a career of the Poles after the return of Bydgoszcz to Poland in 1920. The article concerns business activity of Edmund, Władysław and Czesław Matecki.